2015
DOI: 10.1007/s12253-015-9997-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Hu-Antigen Receptor (HuR) and Cyclooxygenase-2 (COX-2) Expression in Human Malignant and Benign Thyroid Lesions

Abstract: Hu-antigen R (HuR) is considered to play a crucial role in tumor formation and growth by binding to mRNAs encoding proteins such as Cyclooxygenase-2 (COX-2) and inducing their expression via mRNA stabilization and/or altered translation. The present study aimed to evaluate the clinical significance of HuR and COX-2 proteins’ expression in human benign and malignant thyroid lesions. HuR and COX-2 proteins’ expression was assessed immunohistochemically on paraffin-embedded thyroid tissues obtained from 98 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 48 publications
1
16
0
3
Order By: Relevance
“…Thus, strong cytoplasmic HuR expression was a marker of metastatic potential in pheochromocytomas and paragangliomas. Increased HuR protein expression has been evident in many other malignancies, e.g., in breast , ovarian , colorectal , gastric , and oral cancers , in malignant mesothelioma , Merkel cell carcinomas , and thyroid . In most studies, the increased HuR protein expression has been localized to the cytoplasm, and our present findings are in line with that finding.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, strong cytoplasmic HuR expression was a marker of metastatic potential in pheochromocytomas and paragangliomas. Increased HuR protein expression has been evident in many other malignancies, e.g., in breast , ovarian , colorectal , gastric , and oral cancers , in malignant mesothelioma , Merkel cell carcinomas , and thyroid . In most studies, the increased HuR protein expression has been localized to the cytoplasm, and our present findings are in line with that finding.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, HuR and COX-2 expression was classified as low; if the total score was 0 or 2 and high; if the total score was ≥3. In this way, we ensure that each group has a more homogeneous and sufficient number of cases in order to be comparable with the other groups [19,36,37,39]. Staining for ER and PR was evaluated according to CAP/ ASCO recommendations, i.e.…”
Section: Evaluation Of Immunohistochemistrymentioning
confidence: 99%
“…The fraction of HER2 positive stained cells was scored according to CAP/ASCO guidelines [41]. Ki-67 immunoreactivity was classified according to the percentage of positively stained breast cancer cells exceeded the median percentage value into two categories (below and over mean value), as previously reported [19,36,37,39].…”
Section: Evaluation Of Immunohistochemistrymentioning
confidence: 99%
“…They concluded that COX-2 overexpression may be an early event in thyroid neoplasm progression, and COX-2 may promote carcinogenesis by inducing it (30). A recent study reported that COX-2 might be associated with malignant thyroid neoplasia and could be used in the diagnosis of malignant thyroid tumors (31). In vitro studies of thyroid cancer cell lines demonstrated inhibition of proliferation, reduction in cellular migration, and invasion of COX-2 by a selective inhibitor (32,33).…”
Section: Discussionmentioning
confidence: 99%